Impact of trading companies jointly sponsored by rubber board and Rubber Producers societies on growers in Kottayam and Thrissur Districts - Radhakrishnan TP (Department of Plantation Crops and Spices, College of Hrticulture, 1997)
The impact of trading companies on growers in Kottayam and Thrissur districts was studied. The activities of both the companies include centralised marketing of rubber sheet/ latex and centralised purchase and distribution of estate inputs in order to get maximum ben- efits to growers. . The study revealed that the performance of M/s. Manimalayar Rubbers (P) Ltd. was comparative I y better when compared to M/s. Vallathol Rubbers (P) Ltd. The growers of both companies got reasonable price for their produce (field latex or sheet). Both the companies had distributed estate inputs to growers at a reasonably lower price when compared to the open market. Both the companies could make arrangements to supply the estate inputs at the door steps of RPSs without additional charge. Both the companies participated along with Rubber Board officials in the dessemination of scientific knowledge of cultivation. The major limitations found in the functioning of the, RPSs were (1) they do not own building and (2) non co-operation among members. Major suggestions to improve the activities of the company included (1) starting sheet trading and (2) starting rubber based industry or processing unit. The studies indicated that the following suggestions are to be taken to improve the functioning of the companies (1) increasing the paid up share capital (2) taking initative to start either rubber based industry based on mother unit concept or a processing unit or making good quality sheets (3) centralized I region wise bulk purchasing of all estate inputs.